Efficient Gene Editing in Pluripotent Stem Cells by Bacterial Injection of Transcription Activator‐Like Effector Nuclease Proteins. (10th June 2015) - Jia, Jingyue; Bai, Fang; Jin, Yongxin; Santostefano, Katherine E.; Ha, Un-Hwan; Wu, Donghai; Wu, Weihui; Terada, Naohiro; Jin, Shouguang
Abstract : The method of bacterial type III secretion system (T3SS)‐mediated transcription activator‐like effector nuclease (TALEN) protein injection and transfection of an oligonucleotide template to effectively generate precise genetic modifications in stem cells. T3SS‐mediated TALEN protein delivery provides a highly efficient alternative for introducing precise gene editing within pluripotent stem cells for the purpose of disease genotype‐phenotype relationship studies and cellular replacement therapies. Abstract : The type III secretion system (T3SS) of Pseudomonas aeruginosa is a powerful tool for direct protein delivery into mammalian cells and has successfully been used to deliver various exogenous proteins into mammalian cells. In the present study, transcription activator‐like effector nuclease (TALEN) proteins have been efficiently delivered using the P. aeruginosa T3SS into mouse embryonic stem cells (mESCs), human ESCs (hESCs), and human induced pluripotent stem cells (hiPSCs) for genome editing. This bacterial delivery system offers an alternative method of TALEN delivery that is highly efficient in cleavage of the chromosomal target and presumably safer by avoiding plasmid DNA introduction. We combined the method of bacterial T3SS‐mediated TALEN protein injection and transfection of an oligonucleotide template to effectively generate precise genetic modifications in the stem cells. Initially, we efficiently edited a single‐base in the gfp gene of a mESC line to silence green fluorescent protein (GFP) production. The resulting GFP‐negative mESC was cloned from a single cell and subsequently mutated back to a GFP‐positive mESC line. Using the same approach, the gfp gene was also effectively knocked out in hESCs. In addition, a defined single‐base edition was effectively introduced into the X‐chromosome‐linked HPRT1 gene in hiPSCs, generating an in vitro model of Lesch‐Nyhan syndrome. T3SS‐mediated TALEN protein delivery provides a highly efficient alternative for introducing precise gene editing within pluripotent stem cells for the purpose of disease genotype‐phenotype relationship studies and cellular replacement therapies. Significance: The present study describes a novel and powerful tool for the delivery of the genome editing enzyme transcription activator‐like effector nuclease (TALEN) directly into pluripotent stem cells (PSCs), achieving desired base changes on the genomes of PSCs with high efficiency. This novel approach uses bacteria as a protein delivery tool. It is easy to manipulate and adaptable to scaling up. This is a safe delivery system, because the delivery strains can be easily eliminated using simple antibiotic treatment. Type III secretion system (T3SS)‐mediated TALEN protein delivery provides a highly efficient alternative for introducing precise gene alterations within PSCs for the purpose of disease genotype‐phenotype relationship studies and cellular replacement therapies. The results of the present study also pave the way to applying the bacterial T3SS to deliver transcriptional factors into PSCs for cellular reprogramming, raising the hope of a safe technology that can be used in cell or tissue replacement therapy for human genetic diseases.